Göçmenlerle Sosyal Hizmet: Mikro, Mezzo ve Makro Uygulamalar - Attepe Özden, Seda; Bekiroğlu, Seval (Göç ve Sosyal Hizmet, 2023)
The phenomenon of migration affects the whole world. According to the United Nations, more than 200 million people currently live outside their home countries. Whether voluntary or compulsory, the migration process for individuals has many difficulties. Immigrants experience many difficulties in accessing the most basic services such as housing, health and education and social adaptation, as well as many mental health problems. In solving these problems, the need for the social work profession and its practices is increasing day by day, especially with the significantly increasing number of immigrants in the world. Social workers play an important role in solving the problems experienced by immigrants with micro, mezzo and macro practices within the framework of rights-based and generalist approaches. Micro-level practices include a holistic assessment of the problems and needs of immigrant individuals and their families, mediation to meet their needs, psychosocial support to improve mental health, trauma interventions, training and counselling. Mezzo-level practices include developing immigrants' social networks, organizing socio-cultural events, organizing and coordinating volunteer activities, developing social support systems, and group work. Macro-level practices include ensuring the social integration of immigrants, combating stigma and discrimination, carrying out advocacy and public information activities to empower immigrants, contributing to the creation of services and policies, increasing the functionality of institutions, conducting research on the immigrants and dissemination and training of personnel working with immigrants. Social workers working with immigrants use their cultural competencies in their interventions at all levels. They regularly update their knowledge about the problems experienced by immigrants, the services provided to immigrants, and changes in legislation and policies. They contribute to the development of services and policies for immigrants. While doing this, they listen to the voices of immigrants.